Utilización de harina de alfalfa medicago sativa como pigmentante en el engorde de pollos parrilleros - Romero Espinoza, Alexander Vicente (2014)
The work was conducted at the poultry farm "El Gato" platanillos sector , Canton Piñas, Province of Gold The objectives of this research were:1. To determine the effect of pigmentation of broilers tarsi Alfarina implemented in feed.2. Two. Set feed intake, mortality, feed conversion of chickens and get production costs / kg. meat.3. Three. Determine digestive disorders, Alfarina percentages in appropriate formulations.We used a completely randomized design with 4 treatments and 3 replications. 360 chicks were used 1 day of age were distributed homogeneously in 12 galponcillos of 2 x 2m each to 49 days old. The groups were of 30 chicks each.The treatments used were the control and the 5, 10, 15% Alfarina.To measure the pigmentation in the last week we used the colorimeter range of DMS, was measured at all the birds and then averaged.Variables to measure feed intake, weight gain and feed conversion, birds were weighed weekly until the end of the trial.From the results we reached the following conclusions:The highest percentage of pigmentation was obtained in the treatment T2 of Alfarina.The group that consumed less food was the witness.The largest group was the control weight had followed the T2 of Alfarina.Most useful are achieved with T2 Alfarina ($ 158.23).The highest mortality rate obtained was of witness.